SENSORI PIKEL UBIJALAR UNGU (Ipomoea batatas L.) YANG DIFERMENTASI SPONTAN PADA BERBAGAI TINGKAT KONSENTRASI GARAM - Neti Yuliana; Siti Nurdjanah (Jurnal Teknologi & Industri Hasil Pertanian, 2009)
This research was aimed to determine the sensory properties of purple sweet potato pickles which was spontaneously fermented for12 days at various salt concentrations (1%, 2%, 3%, 4%, 5% and 6%).  The results showed that the increase of salt concentrations from 1% to 6% significantly increased sensory acceptability of  purple sweet potato pickles. The best sensory  properties were obtained from  pickle with salt concentrations of 5% - 6%. The score of the color approaching 5 (somewhat like, and described as pink). The score of the texture was close to 3 (somewhat like, and described as hard). The score of the taste close to 4 (moderate, and described as salty). The score of the aroma close to 4 (moderate, and described as slightly acid to acid. The score of the overall acceptance was close to 4 (moderate). Keywords :  pickles, purple sweet potato